The effect of location on the distribution of withdrawals from selected ATMs of the "Euronet" network - Gurgul, Henryk; Suder, Marcin (Managerial Economics, 2014)
Information about the distribution of withdrawals is very essential for ATM networks. It supports optimization of the replenishment process for ATMs. The conducted research showed that the daily distribution of withdrawals was similar among the examined ATMs owned by the Euronet company. Location was the main factor in determining empirical distribution on the same days of the week. Logistic distribution fit best to withdrawals from ATMs located in shopping centers, bank branches, shops, and supermarkets. In addition, uniform distribution was found to be the best alternative for withdrawals from ATMs operating at petrol stations.